A Paulownia fafaj magyarországi termesztésének és felhasználásának lehetőségei - Bodó Máté (2015)
Biomass is a sustainable and competitive renewable energy source in Hungary. Biomass is one of the most promising energy options, since Hungary has excellent agro-ecological conditions for the competitive production of biomass, which is suitable for heat- and power production and also production of fuel. In the topic of Paulownia plantations (permission, planting, treatment, harvesting, wood utilization etc.) there are still a number of open questions in our country. Therefore, the thesis deals with the production and use of Paulownia wood possibilities. In the dissertation Paulownia tree has been analysed using scientific literature and field survey data. The legal background of plantations as well as the invasiveness evaluation, and economic analysis about the plantations.